Factores de riesgo para cáncer de piel en habitantes de la parroquia Capiro, del cantón Piñas, provincia de El Oro - Ramírez Abarca, María Fernanda (2023)
Skin cancer is one of the diseases of greatest concern worldwide due to the increase in the population affected, however, it has not been given the necessary importance to prevent and treat it in a timely manner. The objective of the current work is to identify the risk factors that the inhabitants of the Capiro parish, Piñas Canton, El Oro province have to develop skin cancer. A descriptive, observational, prospective study was carried out, where a previously validated questionnaire was used for data collection, which addresses all the known factors that can increase a person's risk of suffering from skin neoplasms, determining that, if the result obtained is greater than or equal to 5, it is a person with high risk. The study was applied to 84 inhabitants of the aforementioned parish. The results obtained showed that in the population the male sex predominates in 54.76%, 53.57% are dedicated to agriculture, 47.61% belong to phototype III, with a high solar exposure 83.33% in addition, 76.19% of the observed population presents a high risk of developing skin cancer. It was concluded that the risk is due to a greater extent to high sun exposure, so it is necessary to carry out education and monitoring of this population